Fundamental Frequency in Speaking, Singing, Reading and Phonation - NP, Nataraja; A, Jagadish; PJ, Kumar (Journal of All India Institute of Speech and Hearing)
The importance of measurement of fundamental frequency of voice (habitual frequency) in the diagnosis and treatment of voice disorders is well known. Different types of speech samples have been considered by different investigators for this purpose. In the present study an attempt has been made to note the differences in fundamental frequency in speaking, singing, reading and phonation in 30 males and 30 females, using a pitch analyzer. The results indicate that there are significant differences between each type of speech sample considered, in terms of fundamental frequency. The fundamental frequency used in phonation by these subjects has been found to be in the vicinity of optimum pitch.